Nitrogenase (nifH) gene expression in diazotrophic cyanobacteria in the Tropical North Atlantic in response to nutrient amendments - Turk-Kubo, Kendra A.; Achilles, Katherine M.; Serros, Tracy R.; Ochiai, Mari; Montoya, Joseph P.; Zehr, Jonathan P. (Frontiers in Microbiology, 2012)
The Tropical North Atlantic (TNAtl) plays a critical role in the marine nitrogen cycle, as it supports high rates of biological nitrogen (N2) fixation, yet it is unclear whether this process is limited by the availability of iron (Fe), phosphate (P) or is co-limited by both. In order to investigate the impact of nutrient limitation on the N2-fixing microorganisms (diazotrophs) in the TNAtl, trace metal clean nutrient amendment experiments were conducted, and the expression of nitrogenase (nifH) in cyanobacterial diazotrophs in response to the addition of Fe, P, or Fe+P was measured using quantitative PCR. To provide context, N2 fixation rates associated with the <10 μm community and diel nifH expression in natural cyanobacterial populations were measured. In the western TNAtl, nifH expression in Crocosphaera, Trichodesmium, and Richelia was stimulated by Fe and Fe+P additions, but not by P, implying that diazotrophs may be Fe-limited in this region. In the eastern TNAtl, nifH expression in unicellular cyanobacteria UCYN-A and Crocosphaera was stimulated by P, implying P-limitation. In equatorial waters, nifH expression in Trichodesmium was highest in Fe+P treatments, implying co-limitation in this region. Nutrient additions did not measurably stimulate N2 fixation rates in the <10 μm fraction in most of the experiments, even when upregulation of nifH expression was evident. These results demonstrate the utility of using gene expression to investigate the physiological state of natural populations of microorganisms, while underscoring the complexity of nutrient limitation on diazotrophy, and providing evidence that diazotroph populations are slow to respond to the addition of limiting nutrients and may be limited by different nutrients on basin-wide spatial scales. This has important implications for our current understanding of controls on N2 fixation in the TNAtl and may partially explain why it appears to be intermittently limited by Fe, P, or both.